The Meaning Of Symbols In The Acculturation Of Malay Islamic And Chinese Cultures In The Architecture Of The Old Mosque In Gang Bengkok Medan City (Analysis From The Perspective Of Roland Barthes’ Semiotics Theory) - Ulfi Fatharani; Roibin; Fakhruddin (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2025)
Thesis,This study aims to reveal the meaning of symbols in the process of acculturation between Malay and Chinese Islamic cultures in the architecture of the Old Mosque on Gang Bengkok Street in Medan, as well as to understand how these symbols are interpreted by the community and Generation Z. The main issue examined is how architectural elements resulting from the encounter between these two cultures function as signs and form meaning at the denotative, connotative, and mythical levels according to Roland Barthes' semiotic theory. This study uses a descriptive qualitative method through in depth interviews, field observations, and documentation, which are then analyzed using Barthes' semiotic framework. The results show that architectural elements such as temple style roofs, hanging bee ornaments, green and yellow colors, main pillars, and circular motifs form a system of signs that reflect harmony, egalitarianism, and the collective identity of the Malay and Chinese community. The discussion also found that the local community responded positively to this acculturation and turned it into a social myth about cross ethnic harmony, while Generation Z interpreted these symbols as part of a relevant cultural heritage that needs to be preserved. This research confirms that the architecture of the Old Mosque of Gang Bengkok not only functions as a place of worship but also as a representation of a living multicultural narrative that is passed down from generation to generation.